Evaluating the Diagnostic Accuracy of C-Reactive Protein in Diagnosing Pneumonia in Children Using Blood Culture as the Gold Standard: C-Reactive Protein in Diagnosing Pneumonia - Ayaz, Nasir; Ilyas, Adeela; Iqbal, Aneesa; Ullah, Inam; Khan, Iftikhar; Mehmood, Iffat (Pakistan Journal of Health Sciences, 2024)
C-Reactive Protein (CRP) is important in identifying and evaluating bacterial infections as a conventional biomarker. Objective: To determine the diagnostic accuracy of CRP in diagnosing pneumonia keeping blood culture and radiological findings as a gold standard. Methods: A descriptive cross-sectional study was conducted in the Department of Pediatrics at Lady Reading Hospital, Peshawar Pakistan from December 2022 to December 2023. After selecting 246 patients who satisfied the required inclusion criteria for pneumonia, an immunoturbidimetric assay was utilized to quantitatively measure CRP levels. To compare the results to those of the gold standard of blood culture, patients with both positive and negative cultures were included. Among the 246, the mean age of the children was 9±2.73 years. There were 136 males (55%) and 110 females (45%), with male to female ratio of 1.24:1. Results: Results were true positive in 207 (84.15%), true negative in 7 (2.85%), false positive in 9 (3.66%) and false negative in 23 (9.35%). Diagnostic accuracy was analyzed as CRP had a sensitivity of 87.77%, specificity of 52.94%, Positive predictive value of 96%, negative predictive value of 24.32%, and overall diagnostic accuracy was 85.36%. Conclusions: Clinicians and laboratory professionals face difficulties in making a precise and prompt diagnosis of pneumonia. However, by conducting a single, inexpensive, and rapid test using CRP as a qualitative estimator, physicians can prevent the unnecessary use of antibiotics with an accuracy of 85.36%.